Uji potensi kombinasi salep dari ekstrak Cymbopogon citratus, Ruellia tuberosa, dan Aloe vera terhadap tungau Sarcoptes scabiei - Al Fajar, Beni; Putri, Aprilia Kartika; Fajri, Rahmatul (JURNAL BIOLOGICA SAMUDRA, 2024)
Scabies is a zoonotic disease caused by an infestation of the ectoparasite Sarcoptes scabiei var hominis. Chemical-based drugs are commonly used to prevent scabies outbreaks; however, prolonged use of these drugs can lead to adverse effects. This study aims to explore the potential of natural ingredients, namely Cymbopogon citratus, Ruellia tuberosa, and Aloe vera, as alternative treatments to eliminate S. scabiei at a 5% extract concentration. The parameters observed included quality testing, organoleptic properties, homogeneity, pH, and spreadability of the sample preparation (ointment) through descriptive analysis. The results showed that the ointment sample met the required standards for quality, organoleptic properties, homogeneity, pH, and spreadability. The use of a 5% lemongrass and Aloe vera ointment was found to be the most effective treatment compared to other formulations, although it was not as effective as 5% permethrin ointment. Thus, natural ingredients such as lemongrass and Aloe vera demonstrate potential for killing mites and improving skin structure affected by S. scabiei infestations